Identification of Dermatophyte Species after Implementation of the In-House MALDI-TOF MS Database - Calderaro, Adriana (MDPI, 2014)
Despite that matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry (MS) has become a powerful tool in the clinical microbiology setting, few studies have till now focused on MALDI-TOF MS-based identification of dermatophytes. In this study, we analyze dermatophytes strains isolated from clinical samples by MALDI-TOF MS to supplement the reference database available in our laboratory. Twenty four dermatophytes (13 reference strains and 11 field isolated strains), identified by both conventional and molecular standard procedures, were analyzed by MALDI-TOF MS, and the spectra obtained were used to supplement the available database, limited to a few species. To verify the robustness of the implemented database, 64 clinical isolates other than those used for the implementation were identified by MALDI-TOF MS. The implementation allowed the identification of the species not included in the original database, reinforced the identification of the species already present and correctly identified those within the Trichophyton mentagrophytes complex previously classified as Trichophyton. tonsurans by MALDI-TOF MS. The dendrogram obtained by analyzing the proteic profiles of the different species of dermatophytes reflected their taxonomy, showing moreover, in some cases, a different clusterization between the spectra already present in the database and those newly added. In this study, MALDI-TOF MS proved to be a useful tool suitable for the identification of dermatophytes for diagnostic purpose.